Breakfast patterns and their association with body mass index in Brazilian adults - Valéria Troncoso Baltar; Diana Barbosa Cunha; Roberta de Oliveira Santos; Dirce Maria Marchioni; Rosely Sichieri (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2018)
The objective was to investigate the relationships between body mass index (BMI), skipping breakfast, and breakfast patterns in Brazilian adults. We analyzed data of 21,003 individuals aged between 20 to 59 from the Brazilian National Dietary Survey 2008-2009. Breakfast was defined as the eating occasion between 5 and 10a.m. with the highest usual food consumption (exceeding 50Kcal/209.2kJ). Dietary patterns were derived by the factor analysis of 18 food groups (usual intake). Controlling for confounders linear regressions of BMI were used to verify the associations considering the survey design. Skipping breakfast was not associated with BMI. Three breakfast patterns were observed (48% variability): Brazilian Northern (positive loading for meats, preparations with corn, eggs, tubers/roots/potatoes, dairy products, savory snacks/crackers, fruit juices/fruit drinks/soy-based drinks); Western (positive for fruit juices/fruit drinks/soy-based drinks, sandwiches/pizza, baked/deep-fried snacks, chocolate/desserts, cakes/cookies) and Brazilian Southeastern (cold cut meat, milk, cheese, coffee/tea, bread). The Brazilian Southeastern pattern was inversely associated with BMI, while the Brazilian Northern pattern was directly associated with it. Therefore, the results suggest a role for breakfast quality in the association with BMI. Thus, a Brazilian Southeastern breakfast usual intake may be inversely associated with BMI.